Common Adult Skin and Soft Tissue Lesions - Trost, Jeffrey G.; Applebaum, Danielle S.; Orengo, Ida (Seminars in Plastic Surgery, 2016)
A strong foundational knowledge of dermatologic disease is crucial for a successful practice in plastic surgery. A plastic surgeon should be able to identify and appreciate common dermatologic diseases that may require medical and/or surgical evaluation and management. In this article, the authors describe epidermal/dermal, infectious, pigmented, and malignant cutaneous lesions that are commonly encountered in practice. Descriptions include the epidemiology, pathogenesis, clinical course, and management options for each type of lesion.
Keywords: dermatology; cutaneous; common; benign; malignant